Implementasi Undang-Undang ITE Dalam Menjamin Kebebasan Berpendapat di Dunia Maya - Nugroho, Andriyanto Adhi; Hermawati, Mutiara; Sandiah, Rara Siti; Aryaputri, Aqila Shafiqa; Feby, Amanda; Siregar, Tiara Rebecca Kezia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the current era of digitalization, freedom of speech can not only be exercised through direct demonstrations but can also be exercised by voicing opinions freely in cyberspace through social media platforms. However, since the enactment of the ITE Law, which regulates various aspects related to electronic information and transactions, this freedom has begun to be strictly limited, followed by sanctions. However, the article does not clearly regulate what specific violations can be sanctioned so that the articles regulated in the ITE Law related to freedom of expression are dubbed rubber articles by the public. With this in mind, this research aims to find out how the implementation of the ITE Law guarantees the right to freedom of expression and what impact the implementation has. The method used by the author is normative juridical with data collection techniques using library methods that use secondary data sources. The result of the research found is that in its implementation in guaranteeing the right to freedom of expression, ITE Law often causes debates among the public due to misunderstandings in the interpretation of articles related to the right to freedom of expression. So that the research hopes that the principles of freedom of expression guaranteed by the ITE Law can be applied fairly and not lopsidedly.